Forecasting the Total Sales and Benefits of Drug Using the Single Exponential Smoothing Method (case Study: Bentar Pharmacy) - Sundariyah; R Dimas Adityo; Arif Arizal (Fakultas Teknik Universitas Bhayangkara, 2019)
Forecasting is an important thing in corporate strategy planning. The Single Exponential smoothing methodis a time series forecasting method. The purpose of the research is to predict the number of sales of Enervon C drugsand the value of profits at the Bentar Pharmacies each month. The study used sales data for 3 years from January2015 to December 2017. The chosen alpha value was 0.5 by having a MAD value of 5.029360202. Forecasting resultsare carried out by the Single Exponential Smoothing method with the smallest error calculation results. MAD valueon the number of sales of Enervon Aktive 30s with α = 0.1 forecasting results 6.9118 with MAD of 7.363601841, α =0.2 forecasting results of 6.0622 with MAD of 5.375139148, α = 0.3 forecasting results of 5.7198 with MAD of5,375139148, α = 0.4 forecasting results 5,3421 with MAD of 5,121971763, α = 0.5 forecasting results 4,9617 withMAD of 5,029360202, α = 0.6 forecasting results 4,5888 with MAD of 5,04912007 , α = 0.7 forecasting results 4.2229with MAD of 5.206054971, α = 0.8 forecasting results of 3.8533 with MAD of 5.385531046, and α = 0.9 forecastingresults of 3.456869004 with MAD of 5.599237215. And the value of drug benefits obtained from forecasting results in2017 by comparing the actual benefits and the benefits of forecasting.